Association between temperament and polymorphisms of CRH and leptin in Japanese Black Cattle - Aierqing, Sarengaowa; Nakagawa, Akiko; Bungo, Takashi (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The behavioral trait is one of the important concerns when handling livestock. The objectives of the present study were investigated the possible role of these genes on behavioral traits in Japanese Black cattle (Bos taurus). Materials and Methods: Blood samples were collected for DNA extraction and genotyping was carried out using polymerase chain reaction-restriction fragment length polymorphism method. Two energy metabolism related genes, namely, corticotropin-releasing hormone (CRH) and leptin (LEP) were subjected in this work. Temperaments were evaluated by scores of four behavioral tests. Results: Allele frequencies for the C and G alleles at CRH were 0.25 and 0.75, respectively. For the LEP SNP, the C and T alleles were 0.71 and 0.29, respectively. By analyzing the association between the polymorphisms and temperament scores of behavioral tests, significant effects of CRH polymorphism and interaction were not detected but cattle with wild homo-type of LEP tended to permit the contact of stranger when feeding (p < 0.1). Conclusion: These findings suggest that the LEP polymorphism is involved in behavioral traits in Japanese Black cattle. The LEP polymorphism may be useful in selecting Japanese Black cattle with the trait of being docility. J. Adv. Vet. Anim. Res., 7(1): 1-5, March 2020